THE STUDENTSâ PERCEPTIONS TOWARDS AUTHENTIC MATERIALS FOR READING AND LISTENING ACTIVITIES - Halim, Abdul; Mukminatien, Nur; Anugerahwati, Mirjam (STKIP Bina Bangsa Getsempena Banda Aceh, 2018)
AbstractThis paper was aimed at investigating the studentsâ perceptions towards authentic materials in reading and listening activities. In addition, this study also surveyed the studentsâ preferred materials for both listening and reading activities for future classes. The learning of English has been evolving from using traditional media to more advanced and technology-friendly media. One of the media that is very accessible with the support of wide internet access nowadays is online authentic materials. With all the benefits of authentic materials and the use of technology in classroom activities, an English teacher at SMAN 10 Samarinda had been utilizing authentic materials for the past semester. A case study design was employed. The case was considered unique that the school is eminence with good student intake and the quality of student outcomes in academic achievement. Based on a pilot study, there was a need of supplementing the materials with authentic texts. It was for three reasons; first, there was tendency from the students to underestimate the lesson because the lesson, for them, was easy. Second, the book was not enough to prepare them for the national exam (UN) and real communication. Third, they often ran out of materials when they only used the studentsâ book. The data was collected through questionnaires and semi-structured interview. The questionnaires were spread to 50 high school students from 2 accessible classes at the institution. After that, the data was analyzed. First findings from the questionnaire became the base for developing interview sessions with the students to get in-depth perspective of certain answers from them. The findings of how the students perceive the use of authentic materials were discussed. Finally, some suggestions to related significance were also proposed.Â Keywords: Authentic Materials, Listening, Reading